'I can't see any reason for stopping doing anything, but I might have to do it differently'--restoring hope to patients with persistent non-specific low back pain--a qualitative study. - Toye, F; Barker, K (2012)
PURPOSE: To explore the differences in narrative between patients with persistent non-specific low back pain (PLBP) who benefited from a pain management programme, and those who did not benefit. METHOD: We conducted interviews with 20 patients attending a pain management programme; prior to attending the programme, immediately following the programme and at one year. Our analysis focused on a theoretical sample of patients who either described dramatic life improvements at one year, and who described themselves as much worse. We used the methods of grounded theory. RESULTS: We found that finding hope was central to good outcome. Patients restored hope by making certain changes; (a) deconstructing specific fears, (b) constructing an acceptable explanatory model (c) reconstructing self identity by making acceptable changes. Those who had not restored hope retained fears of loss of self, remained committed to the biomedical model and were unable to make acceptable changes. CONCLUSIONS: Our findings may help to operationalise the restoration of hope in patients with PLBP. Firstly, health care professionals need to identify and resolve any specific fears of movement. Secondly, patients need an acceptable explanatory model that fits their experience and personal narrative. Finally our study confirms the centrality of self concept to recovery.